2008
DOI: 10.2174/138920008786049258
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Metabolism: An Analytical Perspective

Abstract: Benzodiazepines are currently among the most frequently prescribed drugs all over the world. They act as anxiolytics, sedatives, hypnotics, amnesics, antiepileptics and muscle relaxants. Despite their common chemical scaffold, these drugs differ in their pharmacokinetic and metabolic properties. In particular, they are biotransformed by different cytochrome P450 isoforms and also by different UDP-glucuronosyltransferase subtypes. The most important studies on the metabolic characteristics of several 1,4-benzod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 120 publications
(166 reference statements)
1
85
0
5
Order By: Relevance
“…A meta-analysis has confirmed that midazolam by any route is superior to diazepam (McMullan et al, 2010). Midazolam offers several unique advantages over other benzodiazepines, including its rapid onset of action, short duration, water solubility, and extended shelf life (Mandrioli et al, 2008). Midazolam has a maximum shelf life of 2-3 years at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis has confirmed that midazolam by any route is superior to diazepam (McMullan et al, 2010). Midazolam offers several unique advantages over other benzodiazepines, including its rapid onset of action, short duration, water solubility, and extended shelf life (Mandrioli et al, 2008). Midazolam has a maximum shelf life of 2-3 years at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam is a benzodiazepine antiseizure agent with rapid onset and short duration of action (Mandrioli et al, 2008). It is administered intravenously or intramuscularly to control acute seizures and status epilepticus (Galvin and Jelinek, 1987;Silbergleit et al, 2011;Reddy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it possesses anticonvulsant, hypnotic and skeletal muscle relaxant properties. The pharmacological action of diazepam enhances the effect of the neurotransmitter GABA by binding to the benzodiazepine site on the GABA A receptor (via the constituent chlorine atom) leading to central nervous system depression [1,2]. The structure of the title compound has been reported earlier [3], however, at room temperature only.…”
Section: Discussionmentioning
confidence: 99%
“…Pluronic F127 is widely used as a thermosensitive gelling agent since it is non-toxic, non-irritating, poses good release characteristics and biocompatible with other chemicals. 2,3 In the present investigation, mucilage isolated from Hibiscus flowers (Hibiscus rosa sinensis) was used as a mucoadhesive agent along with Pluronic F127 to prepare mucoadhesive in situ nasal gels containing alprazolam and to characterise them accordingly, in terms of texture profile analysis, viscosity, mucoadhesive strength, in vitro release profile, in vivo absorption kinetics and histological studies. Mucilages isolated from Hibiscus rosa used in formulations is compared with synthetic polymers hydroxypropyl methyl cellulose (HPMC) and Carbopol 934 (C-934).…”
Section: Introductionmentioning
confidence: 99%